Research on dynamic migration of critical virtual machines for multi-tenancy - Shuo ZHAO; Xin-sheng JI; Guo-zhen CHENG; Yu-xing MAO (网络与信息安全学报)
A dynamic migration method of critical virtual machines for multi-tenancy was proposed.Firstly,the tenants can set ratio of critical virtual machines according to tenant's security requirements,then the dynamic migration frequency of virtual machines were maximized by the coexistence time constraints between virtual machines,finally the migration cost was minimized as an object function for the virtual machines migrated to further reduce the migration cost.Simulation experiments demonstrate that the proposed approach can reduce the impact on the performance of network services and the cost of virtual machines migration,and is more suitable for large-scale network scenarios under the premise of effective defense side-channel attacks.